Hype or hope? High placebo response in major depression treatment with ketamine and esketamine: a systematic review and meta-analysis - Matsingos, Alexandros; Wilhelm, Marcel; Noor, Laila; Yildiz, Cüneyt; Rief, Winfried; Hofmann, Stefan G.; Falkenberg, Irina; Kircher, Tilo (Frontiers in Psychiatry, 2024)
Background: Ketamine and esketamine offer a novel approach in the pharmacological treatment of major depressive disorder (MDD). This meta-analysis aimed to investigate the placebo response in double-blind, randomized controlled studies (RCTs) on patients with MDD receiving ketamine or esketamine. Methods: For this systematic review and meta-analysis Medline (PubMed), Cochrane Central Register of Controlled Trials (CENTRAL), PsycInfo and Embase databases were systematically searched for citations published up to March 17, 2023. A total number of 5017 abstracts was identified. Quality of the included trials was assessed with the Cochrane risk-of-bias tool. The meta-analysis was performed using a restricted maximum likelihood model. This study is registered with PROSPERO, number CRD42022377591. Results: A total number of 14 studies and 1100 participants (593 in the medication group and 507 in the placebo group) meeting the inclusion criteria were selected. We estimated the pooled effect sizes of the overall placebo (dpl = -1.85 [CI 95%: -2.9 to -0.79] and overall treatment (dtr = -2.57; [CI 95 % -3.36 to -1.78]) response. The overall placebo response accounts for up to 72% of the overall treatment response. Furthermore, we performed subgroup analysis of 8 studies for the for the 7 days post-intervention timepoint. Seven days post-intervention the placebo response (dpl 7d = -1.98 [CI 95%: -3.26 to -0.69]) accounts for 66 % of the treatment response (dtr 7d = - 3.01 [CI 95%, -4.28 to -1.74]). Conclusions: Ketamine and esketamine show large antidepressant effects. However, our findings suggest that the placebo response plays a significant role in the antidepressant response and should be used for the benefit of the patients in clinical practice.